Addressing neglected tropical diseases in Africa: a health equity perspective - Nsikakabasi Samuel George; Success Chekwube David; Maxencia Nabiryo; Blessing Abai Sunday; Omotayo Faith Olanrewaju; Yonah Yangaza; Deborah Oluwaseun Shomuyiwa (BMC, 2023)
Abstract Africa accounts for over one-third of the global burden of neglected tropical diseases (NTDs). Although continental efforts have been made to combat these diseases, there still exists a significant gap in the fight, ranging from a lack of data to multisectoral participation and, most critically, health inequity. Here, we assess the effort made to combat challenges caused by health disparities to prevent and control neglected tropical diseases. This article engages a health equity view to addressing the need for inclusion in achieving universal health coverage towards eradicating NTDs and outlines strategies to achieve such. Health disparities exist, and there is substantial and irrefutable evidence for them. Inequitable distribution and limited access to basic and essential life resources such as water, housing, toilets, soap, and literacy continue to facilitate the existence of NTDs such as Schistosomiasis, soil-transmitted helminths, and trachoma, the occurrence of which can be avoided if affected populations have better access to those resources. To eradicate NTDs, health disparities must be addressed to provide excellent health care to all populations and adequate universal health coverage for long-term sustainability. NTD programmes need to be data-driven to ensure better decision-making and ensure the inclusion of diverse population groups including women, children, and youths. This will ensure that no one is left behind, drawing upon the sustainable development goals. Community participation and engagement should also be considered as an essential approach to ensure people are at the centre of health programmes and their implementation.